THE EFFICACY OF DUTASTERIDE AND GREEN TEA TOWARDS BLEEDING ON BPH AFTER TURP: STUDY THEIR EFFECT ON HIF-1α EXPRESSION & HEMATOCRIT - Irawan, Andry; Riwanto, Ignatius; Nugroho, Eriawan Agung (Indonesian Journal of Urology, 2017)
Objective: This study proves differentiation of the combination of dutasteride and green tea, dutasteride, green tea, and placebo alone and their association with differences in hematocrit levels and the expression of hypoxia induced factor-1 alpha (HIF-1α) in patients with Benign Prostate Hyperplasia (BPH) were performed Trans urethral resection of the prostate (TURP) surgery. Material & method: Experimental study with the draft "randomized control trial". Comparing angiogenesis changes between groups of BPH patients who underwent TURP surgery to assess the expression of HIF-1α and Δ Ht (Hematocrit) after administration of dutasteride, green tea with combination of dutasteride and green tea for 14 days. Results: The combination of dutasteride and green tea was not significant in reducing the expression of HIF-1α. Mean P1 group (59.32 ± 14.69); P2 group (59.11 ± 20.73); P3 group (64.21 ± 14.95); K group (58.16 ± 16.00). Kruskal test results obtained p=0.491 walis which means the difference percentage of HIF-1α among the 4 groups was not significant. The mean Δ Ht P1 group (0.61 ± 0.204); P2 group (0.54 ± 0.250); P3 group (0.41 ± 0.275); group K (0.41 ± 0.275). In statistical test with Mann Whitney test comparing the percentage reduction obtained Ht levels dutasteride group against group of green tea obtained p=0.213 means that there is no significant difference. Where a significant difference to the other groups. Conclusion: The combination of dutasteride and green tea for 14 days before TURP surgery does not reduce the expression of HIF-1α in BPH patients who underwent TURP surgery. Δ Ht significant decline in the combination group compared with other groups and might be influenced by several factors during TURP surgery.